2019
DOI: 10.1007/s00198-019-05230-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bone loss in proximal femurs of postmenopausal osteoporotic women with AGN1 local osteo-enhancement procedure (LOEP) increases hip bone mineral density and hip strength: a long-term prospective cohort study

Abstract: This first-inhuman study of AGN1 LOEP demonstrated that this minimally-invasive treatment durably increased aBMD in femurs of osteoporotic postmenopausal women. AGN1 resorption was coupled with new bone formation by 12 weeks and that new bone was maintained for at least 5-7 years resulting in substantially increased FEA-estimated femoral strength. Introduction This first-inhuman study evaluated feasibility, safety, and in vivo response to treating proximal femurs of postmenopausal osteoporotic women with a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 32 publications
(46 reference statements)
1
18
1
1
Order By: Relevance
“…Further, a second hip fracture has an even poorer prognosis than the first 9,10 . Therefore, a thorough risk assessment following a first hip fracture should be performed as a basis for a detailed intervention, for example, to decide between antiresorptive and anabolic therapy, to optimize physical exercise, or to apply local osteo‐enhancement procedures currently undergoing clinical validation 11 …”
Section: Introductionmentioning
confidence: 99%
“…Further, a second hip fracture has an even poorer prognosis than the first 9,10 . Therefore, a thorough risk assessment following a first hip fracture should be performed as a basis for a detailed intervention, for example, to decide between antiresorptive and anabolic therapy, to optimize physical exercise, or to apply local osteo‐enhancement procedures currently undergoing clinical validation 11 …”
Section: Introductionmentioning
confidence: 99%
“… 89 , 91 In 2020, a long-term prospective cohort study on LOEP was published. 92 The authors treated 12 postmenopausal osteoporotic women with femoral LOEP and found that treated femoral neck BMD rapidly increased by 68% as soon as 3 months of follow-up. Interestingly, the FEA-estimated femoral strength increased by 41% in less than 6 months.…”
Section: Future Perspective On Osteoporosis Therapiesmentioning
confidence: 99%
“…Diese als „local osteo-enhancement procedure“ (LOEP) bezeichnete (chirurgische) Intervention wird lokal jeweils einmalig durchgeführt (z. B. am Schenkelhals), hierbei wird das injizierte Material im Verlauf resorbiert und durch eigenen Knochen ersetzt [ 32 ].…”
Section: Zukünftige Entwicklungen – Kombinationstherapie Und Neue Therapieformenunclassified